Quick Evaluation Study on Fourteen (14) Major Development Programmes in Arwal District of Bihar State Affected by Left Wing Extremism (LWE) - Planning Commission (Planning Commission, 2011)
"Background Planning Commission has a strong conviction that Left-Wing Extremism (LWE) in the country is not a mere law and order problem, instead, the socio-economic dimensions of LWE are crucial and there is an urgent need to appropriately address them. In order to get an in-depth understanding of the overall development scenario, AMS was entrusted by the Planning Commission to conduct a quick evaluation of the major development programs in 5 Left Wing Extremism (LWE) affected districts of Bihar, namely, Arwal, Aurangabad, Gaya, Jamui and Jehanabad. The reference period of the evaluation study is three years 2007-08 to 2009-10. The present report pertains to the Arwal district. Methodology In accordance with the sampling methodology suggested by the Planning Commission, 2 blocks were selected in consultation with the Deputy Development Commissioner and the Director of DRDA. From each of the two blocks selected, 5 villages were selected in consultation with the Block Development Officer (BDO). While selecting the villages, it was ensured that these were scattered and not contiguous. The village schedules were administered to any key influential person of the village, such as, PRI members, ANM, AWW, school teacher, etc. From each sample village, a total of 20 households were selected randomly giving priority to the households belonging to the Below the Poverty Line (BPL)/Scheduled Caste/Scheduled Tribe categories. The study schedules for various stakeholders containing a judicious mix of questions seeking quantitative and qualitative information were developed and supplied by the Planning Commission."
"Programme Evaluation Organisation Planning Commission Government Of India New Delhi"